ASSESSMENT OF THE NATURAL MONUMENTS STATE - Klуmenko Mykola; Borshchevska, Iryna; Stetsiuk, Liudmyla; Budnik, Zinaida (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The state of the monuments of the Rivne region was evaluated. A sample of all nature monuments was collected by name of the object: tree, lake, spring, well, marsh, rare plant species, rare animal species, red-book species, sediments and outcrops. Measures and recommendations for improving the state of nature monuments are offered. Nature sites, as nature reserves, are the core of the "ecological framework" of natural regions. Their presence ensures ecological balance. They also play a huge role in ensuring sustainable development, preserving the most unique natural complexes and landscapes, preserving the gene pool of flora and fauna. The main task of nature monuments is to preserve the natural complexes in their natural state. These are unique, valuable in ecological, scientific, cultural and aesthetic terms, natural complexes, as well as objects of natural and artificial origin, for which the special protection regime is established.